Catalytic capacity of diaza-crown ether lanthanum complexes with varied ligands for phosphate ester hydrolysis in different media. (1st November 2016) - Xie, Jia-Qing; Zhang, Ya; Cai, Shu-Lan; Li, Fang-Zhen; Feng, Fa-Mei
Two diaza-crown ether compounds, 1, 4, 10, 13-tetraoxa-7, 16-diazacyclooctadecane (L0) and its derivative with double acetamide side arms 2, 2'-(1, 4, 10, 13-tetraoxa-7, 16-diazacyclooctadecane-7, 16-diyl)diacetamide (L), and the corresponding two lanthanum complexes were synthesised and characterised. The catalytic capacity of the lanthanum complexes was investigated for the hydrolysis of bis(4-nitrophenyl) phosphate ester (BNPP) in aqueous solution and in CTAB micelles. Kinetic studies show that the catalytic efficiency of complex LaL is obviously higher than that of complex LaL0, and introducing acetamide into the ring of the diaza-crown ether can improve the catalytic ability of the complexes for BNPP hydrolysis. A rate enhancement of about two times was observed for the complex–micelle in contrast with the complex–water system for BNPP catalytic hydrolysis. The optimal pH for the catalytic reaction in the two kinds of media systems show an approximately 0.4 pH unit difference. The two complexes possess higher thermostability, and are more stable in the micelle than in aqueous solution. Based on the results and their analysis, a catalytic mechanism with cooperation of acetamide is proposed.